2015
DOI: 10.1016/j.clinthera.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Patient-reported Adherence to Glaucoma Medications on a Visual Analog Scale Compared With Electronic Monitors

Abstract: Purpose Glaucoma medications can reduce intraocular pressure and improve clinical outcomes when patients adhere to their medication regimen. Providers often ask glaucoma patients to self-report their adherence, but the accuracy of this self-report method has received little scientific attention. Our purpose was to compare a self-report medication adherence measure with adherence data collected from Medication Event Monitoring Systems (MEMS) electronic monitors. Additionally, we sought to identify which patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 38 publications
(58 reference statements)
1
20
0
3
Order By: Relevance
“…It is unclear why respondents in this group were predominantly female and how this may have affected the results. Previous research has found that men over-report glaucoma medication adherence in their self-reports compared to adherence timing data collected from electronic monitors [ 23 ]. It is possible that there are gender differences in self-reported adherence to insulin, though additional research is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why respondents in this group were predominantly female and how this may have affected the results. Previous research has found that men over-report glaucoma medication adherence in their self-reports compared to adherence timing data collected from electronic monitors [ 23 ]. It is possible that there are gender differences in self-reported adherence to insulin, though additional research is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…These were used with both twice-daily and fourtimes-daily topical IOP-lowering medications; there was no Hawthorne effect because patients were supplied bottles and were unaware of being monitored [36,37]. Since then, a variety of electronic tools have been developed and used to assess adherence to eyedrops [54,55]. Unfortunately, these tools are primarily used in research and are not widely available for use in clinical practice.…”
Section: Limitations Of the Current Assessment Toolmentioning
confidence: 99%
“…A variety of clinical studies have used a Medication Event Monitoring Systems (MEMS) device. In these scenarios, the eyedrop bottle is placed with a MEMS device that tracks when a patient opens the outer bottle containing the eyedrop bottle [10,55]. One problem with this approach to date has been the short-term nature of the assessment; studies generally range from 1 to 3 months.…”
Section: Limitations Of the Current Assessment Toolmentioning
confidence: 99%
“…Self-reported adherence is known to be over-estimated compared to electronically monitored data. 13 However, using a validated instrument to measure self-reported adherence is still a valuable tool for estimating adherence. Refill adherence is a less costly method of assessing adherence than electronic monitoring and is not subject to the Hawthorne effect or to the bias of self-report.…”
Section: Methodsmentioning
confidence: 99%